Learners in the West, practitioners in the East: an investigation of the teaching experiences of Chinese EFL teachers - Liao, Yifan (Kansas State University, 2022)
Fueled by present-day internationalization and globalization, an unprecedented growing number of Chinese English teachers go to English-speaking countries to pursue graduate degrees in ESL/EFL teacher education programs and return to teach in China. These teachers are the learners in the West and the pioneer practitioners in the East. It is pivotal to understand the nature of these teachers’ learning and teaching experiences. This qualitative study explored the English teaching experiences of Chinese EFL teachers who received professional teacher training in a TESOL program in the United States and returned to their home country. Through phenomenological case study with purposeful and criterion-based sampling, four participants were invited to describe their lived experiences of early English learning, teacher training, and English teaching in China to develop a contextually based understanding of the phenomenon. The data sources included semi-structured interviews and documents. The sociocultural theory was used as the theoretical framework in the study. The findings highlighted the significance of Western TESOL training on teachers in terms of broadening their horizon, developing critical perspectives on viewing the world, empowering their TESOL knowledge, practical knowledge, and themselves as EFL teachers. At the same time, the study discovered the complexity of EFL teaching, considering teachers’ previous learning experiences and various contextual factors. The study will contribute to Western TESOL programs and provide implications for future practice in China.
Keywords: English as a second language; Education; Foreign language education; Pedagogy; Teacher education; Language